2023
DOI: 10.2337/dc22-1760
|View full text |Cite
|
Sign up to set email alerts
|

Severe COVID-19 Infection in Type 1 and Type 2 Diabetes During the First Three Waves in Sweden

Abstract: OBJECTIVE Type 2 diabetes is an established risk factor for hospitalization and death in COVID-19 infection, while findings with respect to type 1 diabetes have been diverging. RESEARCH DESIGN AND METHODS Using nationwide health registries, we identified all patients aged ≥18 years with type 1 and type 2 diabetes in Sweden. Odds ratios (ORs) describe the general and age-specific risk of being hospitalized, need for intensive … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 29 publications
1
3
0
Order By: Relevance
“…In a study covering the initial three waves of the COVID-19 pandemic, researchers observed a significantly higher likelihood of severe COVID-19 outcomes, including hospi-talization, intensive care unit admission, and mortality, in individuals with type 2 diabetes, which corroborates our findings that compared three consecutive years of the pandemic [28]. Notably, younger individuals with type 2 diabetes exhibited disproportionately higher odds for these severe outcomes compared to their older counterparts and the general non-diabetic population.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…In a study covering the initial three waves of the COVID-19 pandemic, researchers observed a significantly higher likelihood of severe COVID-19 outcomes, including hospi-talization, intensive care unit admission, and mortality, in individuals with type 2 diabetes, which corroborates our findings that compared three consecutive years of the pandemic [28]. Notably, younger individuals with type 2 diabetes exhibited disproportionately higher odds for these severe outcomes compared to their older counterparts and the general non-diabetic population.…”
Section: Discussionsupporting
confidence: 90%
“…Thus, our study contributes to the limited information on how COVID-19 affects T1D patients. The prevalence of T1D in our COVID-19 cohort was 31% compared to global reports ranging from 0.15% to 28.98%, illustrating the diverse clinical presentations and outcomes in this patient population [28].…”
Section: Discussionmentioning
confidence: 57%
“…Thirdly, because the exposed group was distinguished from the unexposed group based on the latter not having a positive COVID‐19 PCR test result and not being hospitalized with a COVID‐19–related diagnosis admission code, there remains the possibility of asymptomatic COVID‐19–infected participants, who could not be diagnosed, being included in the control groups. Moreover, while existing studies suggest a difference in risks of COVID‐19 between patients with type 1 diabetes and type 2 diabetes, 45 because of the limited number of patients with a diagnosis of type 1 diabetes in the dataset, the statistical power was insufficient to analyse the risks in patients stratified by type of diabetes. Lastly, because of the limited sample size of COVID‐19 patients with diabetes, especially those with severe disease, associated risks identified for certain disease complications may be affected by low event rates and high CIs.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, patients with diabetes and COVID-19 experience excessive activation of the coagulation system, microthrombus formation, and stagnation of pulmonary circulation, which result in decreased oxygenation. Jon et al proposed that patients with type 2 diabetes are at high risk of severe COVID-19 and therefore increase the ICU occupancy rate [ 34 ]. Patients with type 2 diabetes exhibit high levels of ACE2 receptors, which may extend the cell-binding period of SARS-CoV-2 and increase the viral load and infection severity [ 35 ].…”
Section: Discussionmentioning
confidence: 99%